KAWASAN GALERI BUDAYA SUNGAI DI BANJARBARU - Fatwati, Neti; Wastuty, Prima Widya; Mutia, Indah (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
The lack of cultural tourism in Banjarbaru is concerned to reduce public interest in culture, which is likely to cause the loss of the culture itself. Therefore, the government of Banjarbaru is planning the construction of the Embung Lokudat Green Open Space (RTH), where one of the goals of the development of this open space is to become a tourist destination based on cultural education in South Kalimantan. In the Embung Lokudat green open space, it is necessary to have a supporting area to better reflect the culture of South Kalimantan, where South Kalimantan is identical to the Banjar Tribe, and the Banjar Tribe community has a life that is closely related to the river. The River Culture Gallery area is very suitable to be used as a supporting area for Embung Lokudat Green Open Space because the River Culture Gallery has the function of preserving the river, storing evidence of river culture, and introducing river culture to the public. The design method used is a Responsive Environment with the application of the Story Telling concept to create an interesting and educative River Culture Gallery Area..